Winds of fury Book Three of The Mage Winds - Lackey, Mercedes (DAW Books New York, 1994)
Valdemar is once again in peril, threatened by Ancar of Hardorn, who has long sought to seize control of the kingdom by any means at his command. Yet this time Ancar may well achieve his goal, for by harnessing the power of Mornelithe Falconsbane, the Dark Adept, he has set into motion a magical strike against Valdemar the like of which hasn't been attempted in more than five hundred years - not since Vanyel, the last Herald-Mage, shielded the kingdom from attack by the deadliest of sorceries. And with Valdemar's ancient spell-generated protections finally breaking down, Queen Selenay, Herald-Princess Elspeth, and their people could soon be left defenseless against an enemy armed with spells no one in Valdemar has the knowledge to withstand. But as the long dormant magic of Valdemar begins to awaken, Elspeth finds that she too has a mysterious ally - a powerful spirit from the long-forgotten past. . .
94614
Keywords: Science fiction; Fantasy; Paranormal